Case Report of a Pituitary Metastasis from Lung Adenocarcinoma Masquerading as Pituitary Adenoma - Rajakumar, Radhamani (J ASEAN Fed Endocr Soc, 2020)
Metastasis to the pituitary gland is an unusual situation in clinical practice and is typically observed in those with underlying malignancy with breast and lung being the commonest primary site. However, we report a case of an apparently well 49-year-old female with metastatic lung adenocarcinoma who presented with visual disturbance and diabetes insipidus related to pituitary metastasis as an initial presentation.